THE EFFECT OF RICE HUSK CHARCOAL ON THE REDUCTION OF IRON LEVELS (TOTAL FE) IN DUG WELL WATER IN LHONG RAYA VILLAGE, BANDA RAYA DISTRICT, BANDA ACEH CITY - Chairunnisa; zulfikar, zulfikar; wiwit, Wiwit Aditama; Budi Arianto PS, Budi Arianto PS; Khairunnisa, Khairunnisa (Jurusan Kesehatan Lingkungan, Poltekkes Kemenkes Aceh, 2022)
The bacround Water is a chemical compound that is very important for the life of living things on earth, excessive iron content in water is considered to endanger the life of aquatic organisms. The designation of iron content in clean water is <10 mg/l. The result of burning rice husk produces rice husk charcoal which can be used as adsorbent of heavy metals in water. This was a quasi experimental study, this study was conducted at the researcher's home and in the laboratory of Regional Technical Implementation Unit UPTD on 15 June 2017, the subject of this study was 9 liters of dug well water. The data were obtained directly from the examination results of iron (Total Fe) levels in dug well water. The study results obtained an average amount of Fe content with a dose of 20 grams of -0.265 mg/l, Fe content with a dos0065 of 30 grams of -0.301 mg/l, Fe content with a dose of 40 grams of -0.388 mg / l. From the conclusion, it can be concluded that the most effective dose of rice husk charcoal in lowering iron (total Fe) levels was 40 grams. It is necessary to conduct further study using other methods to lower iron (total Fe) levels to avoid turbidity in the water.